1978
DOI: 10.1021/jf60220a048
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of arabino-galactan from black gram (phaseolus mungo)

Abstract: sample, using relative peak heights from a GLC curve to follow changes in oil composition with maturity.The ratio of octanal to decanal in grapefruit oils has been suggested as a quality index. Kesterson et al. (1971) reported ratios of 1:l.l to 1:1.4 for white grapefruit oil and ratios of 1.2:l to 1.3:l for red grapefruit oil. A later study (Braddock and Kesterson, 1976) indicated that the ratio was greater than 1 in a white grapefruit oil sample. The ratio we found was about 1.2:l.Several of the identified c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…This is also because of combined contribution of both heterofermentative lactobacilli and non LAB (Thyagaraja et al 1992). Since both leavening and acid development are required for 'idli' (Susheelamma and Rao 1978), determination of the end point of the 'idli' fermentation becomes rather arbitrary. However, the use of different ingredients in different proportions resulted in raise in volume besides reduction of fermentation period.…”
Section: Measurement Of Increase In Batter Volume During Natural Fermmentioning
confidence: 99%
“…This is also because of combined contribution of both heterofermentative lactobacilli and non LAB (Thyagaraja et al 1992). Since both leavening and acid development are required for 'idli' (Susheelamma and Rao 1978), determination of the end point of the 'idli' fermentation becomes rather arbitrary. However, the use of different ingredients in different proportions resulted in raise in volume besides reduction of fermentation period.…”
Section: Measurement Of Increase In Batter Volume During Natural Fermmentioning
confidence: 99%
“…The viscosity plays a role in retaining the gases, which cause leavening in the idli batter. This, in turn, is essential for the porosity of the steamed pudding (Susheelama & Rao, 1978). Further it is indicated that increase in viscosity stabilizes the network of foam formed by the surface-active proteins and is essential for raising the batter volume.…”
Section: Article In Pressmentioning
confidence: 99%
“…This may be due to the nature of the grain. Black gram contains a lot of mucilaginous (slimy) matter (Susheelamma & Rao, 1978), which may provide a cushioning effect to the starch granules protecting them from greater damage.…”
Section: Black Grammentioning
confidence: 99%